IDENTIFIKASI DAN ANALISIS FAKTOR PENDORONG DAN FAKTOR PENGHAMBAT MENGGUNAKAN FORCE FIELD ANALYSIS di ARENAN KALIKESEK, KECAMATAN LIMBANGAN, KABUPATEN KENDAL, JAWA TENGAH - Muchlis Adi Susilo, Achmad; Djumiarti, Titik; Afrizal, Teuku (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The tourism sector is one of the highest foreign exchange earners for Indonesia, so continuous development in this sector is crucial. In the development of a tourist attraction, there are both driving and restraining factors. Arenan Kalikesek is a newly established tourist destination in Kendal Regency, having started operations in 2021. However, it still faces several issues, such as the lack of legal framework from the Kendal Regency government, poor accessibility, and inadequate facilities and infrastructure. These issues are closely related to the factors influencing the development of Arenan Kalikesek. This study aims to identify and analyze the factors that support and hinder the development of Arenan Kalikesek based on an internal and external environmental analysis. The research uses John M. Bryson's strategic planning theory, employing a descriptive qualitative research method with Force Field Analysis as the analytical tool to assess the impact of the supporting and restraining factors on the development. The results of the study show that there are six supporting factors and six restraining factors that influence the development of Arenan Kalikesek. After applying Force Field Analysis, it was found that the total weight of the driving factors is higher than that of the restraining factors. The key driving factors are community participation in the management and development of Arenan Kalikesek and the high personal income generated for tourism development, while the key restraining factors are poor road accessibility and the lack of cultural events held at Arenan Kalikesek. The recommendations from the research are to create a proposal for road infrastructure improvements to the Kendal Regency Government, repair and provision of parking areas as well as parking management, establishment of entrance ticket booths, and the organization of an annual cultural event in Arenan Kalikesek by utilizing community participation.